How do you simplify algebra expressions? Hi,I don't think that I can give you rules for what a simplified algebraic expression is. I can however show you an example and suggest some steps that you should try. Suppose that you have the expression = (3 x^{3}  2 x^{3})  x^{2} + (4 x + 2 x) = (32) x^{3}  x^{2} + (4 + 2) x = x^{3}  x^{2} 2 x Next look for common factors. In this expression x is a common factor in each term so you can write = x^{3}  x^{2} 2 x = x(x^{2}  x  2) = x(x^{2}  x  2) = x(x  2)(x + 1) Penny
